Análisis de la planificación financiera de las pequeñas y medianas empresas (pymes) en la ciudad de Quevedo, periodo 2013 - Suárez Portilla, Yuliana Isabel (2013)
The thesis project has focused on "Financial Planning for Small and Medium Enterprises (SMEs) in the city of Quevedo, Period 2013". The search and data collection was performed based on the methods and research techniques, derived from primary and secondary sources. The thesis project investigated it has developed into chapters: First chapter: Focuses on the context and location of the research problem, it is related in a macro, meso and micro, the importance of research, justification, and formulation of objectives and formulation of hypotheses. Second chapter: This chapter develops the theoretical foundations that guide research to the research problem. Third chapter: Discusses the materials and methods used in research, types of research and survey population and sample to be analyzed in the research. Fourth chapter: Contains the interpretation of the results of surveys of SMEs and discussion of evidence and / or disapproval of the hypotheses. Fifth chapter: Is based on the determination of conclusions and recommendations for SMEs. Sixth chapter: This chapter is disclosed references bibliographies of which have been extracted. Seventh chapter: In this chapter we find the tables and graphs of the investigation, and the complement to the outcome of the investigation.